Synthesis and Characterization of Urea–Formaldehyde Eco-Friendly Composite Based On Natural Fibers - Bhandari, Netra Lal; Dhungana, Babu Raj; Lach, Ralf; Henning, Sven; Adhikari, Rameshwar (Journal of Institute of Science and Technology, 2019)
Present work explains the synthesis of urea–formaldehyde composites with Allo (Girardinia diversifolia) and cotton (Gossypium arboreum) fibers. Urea–formaldehyde resin was synthesized by condensation polymerization of urea and formaldehyde monomers. Cellulose fibers were extracted by various chemical treatments of natural fibers. Composites were prepared with neat and extracted cellulose from Allo and cotton fibers by solution casting method. Fibers and composites were characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), optical microscopy (OM), thermo-gravimetric analysis (TGA) and micro-indentation tests. Results showed that composite with treated Allo fibers had better morphological, mechanical and thermal properties than untreated Allo and cotton fibers.